Morphological and growth altering effects of Cisplatin in C. albicans using fluorescence microscopy - Ganesan Natarajan; Raghunathan Malathi; Kesavan Chandrasekhar (BMC, 2005)
Abstract Changes in morphology and growth curve of Candida albicans in response to treatment by Cisplatin has been studied using fluorescence staining with ethidium bromide. Treatment with Cisplatin was found to markedly inhibit hyphae and ovoid growth as revealed by ethidium bromide staining of drug treated cells. These changes were concomitant with inhibitory effects on the growth curve with respect to untreated cells Presence of Cisplatin not only caused suppression in the limiting values in the growth curve, but also caused a slight left shift in the EC50 values. Some of the ovoid cells undergoing poisoning with cisplatin were found to be unusually enlarged before undergoing their natural fate thus suggesting formation of similar cytotoxic end products with DNA.